Need Analysis for Development of Inquiry-Based STEM Materials to Improve Critical Thinking Skills - Nici Jumatul Fitri; Syafriani (Jurnal Penelitian Pendidikan IPA, 2024)
21st-century learning plays an important role in producing quality human resources. One of the skills that students must have to face this century is critical thinking skills. This research aims to determine students' critical thinking skills and find out to what extent the stages of inquiry learning have been implemented, as well as their integration with the STEM approach. The type of research used is survey research. The instruments used were interview guide sheets, tests of student critical thinking skills, observation sheets of learning implementation, and analysis sheets of the interviews conducted with 4 physics teachers in the four schools. The research results show that learning in schools is still conventional (teacher-centered). The integration of the inquiry process with the STEM approach in learning and the teaching materials used is still low. Students' critical thinking skills are also low. Therefore, the recommendation from this preliminary study is that there is a need to develop physics teaching materials that integrate inquiry learning with a STEM approach to improve students' critical thinking skills.